Diagnostic validity of Thoracic trauma severity score in patient with blunt thoracic trauma for predicting mortality rate - Ngakan Gede Dwija Hermawan; I Nyoman Semadi; I Gede Raka Widiana; Desy Permatasari; Christopher Ryalino (Neurologico Spinale Medico Chirurgico, 2019)
Introduction: The high incidence of blunt thoracic trauma is still a serious concern in emergency services. Mild to severe cases of blunt thoracic trauma that come to the emergency department are not those that can be considered simple but need to be reviewed for the possibility that can lead to the occurrence of advanced complications. This study aims to predict mortality in patient with blunt thoracic trauma with TTS (Thoracic trauma severity) score. Patients and Methods: This is a retrospective study with 52 subjects of blunt thoracic trauma patients treated at our University Hospital from January 2016 to May 2017. Eligible data were collected from medical record analyzed by receiver operating characteristics curve and cross tabulation. Results: The age of the subjects are 48.03±15.62, with male 42 subjects (80.8%) and female ten subjects (19.2%). The mean point of Thoracic trauma severity score (TTSS) was 8.32 ± SD: 2.69. The outcome was three patients dead (5.8%) and 49 patients discharged (94,2%). The sensitivity of TTSS 100 %, specificity 89.7%, positive predictive value (PPV) 37.5%, negative predictive value (NPV) 100%, and accuracy rate 90.3%. Highly sensitivity and specificity results for Thoracic Trauma Severity Score is valid for the screening of Blunt Thoracic Trauma. Conclusion: At 11.5 cut-off point, the TTSS was an excellent tool to predict the mortality rate of patients with blunt thoracic trauma. It has a 100% sensitivity and 89.7% specificity, as well as 37.5% PPV and 100% NPV.